Sustained and delayed noisy miner suppression at an avian hotspot. (9th March 2020) - Crates, Ross; Rayner, Laura; Webb, Matthew; Stojanovic, Dejan; Wilkie, Colin; Heinsohn, Robert
Abstract: To mitigate the impact of noisy miners Manorina melanocephala on Australia's woodland birds, there is a need to identify locations where noisy miner suppression can be affordable, sustainable and facilitate woodland bird recovery. In 2017, we suppressed noisy miners from the Goulburn River, NSW for at least three months. During this period, six pairs of critically endangered regent honeyeaters nested in the treatment area. In 2018, we continued monitoring the original noisy miner treatment area, which was expanded to include our 2017 control area, and established a new control area downstream. In 2019, the removal effort was again expanded to include the 2018 control area. In the 2017 treatment area, noisy miners remained suppressed up to 27 months post‐removal. Their numbers here were lower 1 year after the initial cull than in the week after it. In the 2018 and 2019 treatment areas, noisy miner abundance was significantly lower after respective culls than at all pre‐removal periods. In 2018, around 20 vulnerable painted honeyeaters occupied the 2018 treatment area. In 2019, two regent honeyeater pairs nested in and at least 40 painted honeyeaters occupied the treatment area. Songbird abundance increased within seasons and also up to a year following noisy miner removal, and plateaued thereafter. We show how, in strategic locations, a week of noisy miner suppression each spring can sequentially create ever‐larger landscapes where noisy miner impacts on threatened woodland birds are minimal. Abstract :